WARUNG HIK BERTAHAN DALAM PERSAINGAN USAHA DI KOTA KARANGANYAR - Hendarti, Yanita (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
This study aims to determine how the efforts of merchant stalls HIK (traders immigrants from outside the town of Karanganyar) in order to survive in the face of competition in the town of Karanganyar. Improvement of street vendors in the city of Karanganyar significantly from year to year. The increase was supported also by government policies in terms of the provision of land or a trade. Street vendors located in the town of Karanganyar include small food vendors, food stalls, coffee shops, small kiosks and others. One type of vendors who shows the development (in terms of quantity) in the town of Karanganyar is Warung HIK. is a merchant stalls HIK are street vendors (seller men) who sell food and drinks, such as coffee, tea, ginger, some snacks and a lunch pack. They trade on pavements or in front of the shopping center, special for the evening, after the store closed. Based on the results and discussion, it can be concluded that: Traders stall HIK in the town of Karanganyar been able to develop well and able to withstand competition, the ability to grow and survive the competition, in addition driven factors skills and high morale, also driven by involvement of social capital among traders, HIK stalls, stalls in the town of Karanganyar HIK can be classified into three categories, namely merchant stalls HIK independent, semi-independent and non-independent and most buyers find it convenient to stop by to linger in HIK stalls.Keywords: HIK stalls, street vendors, competition